2019
DOI: 10.1186/s12885-018-5231-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age at diagnosis of head and neck cancer on incidence of metachronous cancer

Abstract: BackgroundMetachronous cancer in patients with head and neck cancer (HNC) is common and is associated with a poor prognosis. We aimed to evaluate the incidence of metachronous cancer at different sites according to age at diagnosis of index HNC.MethodsWe collected data on 2011 patients with oral cancer, oropharynx cancer, hypopharyngeal cancer, and laryngeal cancer as index cancers using the Osaka International Cancer Institute Cancer Registry database between 2005 and 2016. Among these, we analyzed 1953 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 23 publications
(30 reference statements)
1
19
0
Order By: Relevance
“…Fukuhara et al retrospectively analyzed 135 patients with primary HNSCC and found that multiple LVLs were significantly associated with the development of metachronous ESCC [ 10 ]. There were two retrospective studies that used big data analysis for the risk of head and neck cancer patients to develop metachronous ESCN in Japan and Taiwan [ 15 , 16 ]. In Japan, Iwatsubo et al used the Osaka International Cancer Institute Cancer Registry database and retrospectively recruited 1953 head and neck patients between 2005 and 2016 [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fukuhara et al retrospectively analyzed 135 patients with primary HNSCC and found that multiple LVLs were significantly associated with the development of metachronous ESCC [ 10 ]. There were two retrospective studies that used big data analysis for the risk of head and neck cancer patients to develop metachronous ESCN in Japan and Taiwan [ 15 , 16 ]. In Japan, Iwatsubo et al used the Osaka International Cancer Institute Cancer Registry database and retrospectively recruited 1953 head and neck patients between 2005 and 2016 [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were two retrospective studies that used big data analysis for the risk of head and neck cancer patients to develop metachronous ESCN in Japan and Taiwan [ 15 , 16 ]. In Japan, Iwatsubo et al used the Osaka International Cancer Institute Cancer Registry database and retrospectively recruited 1953 head and neck patients between 2005 and 2016 [ 15 ]. Younger patients (age < 65 years), histological type (squamous cell carcinoma), and primary lesion location (hypopharynx) were significant risk factors for head and neck cancer patients to develop metachronous ESCNs [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The males and the age range from 45 to 69 years represent a world prevalence of affection with oral cavity and oropharyngeal cancer (15,16) . The data found in this study corroborate such findings.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors argue that the diagnosis of BC bears a theoretical and hypothetical character. Thus, the diagnosis itself remains controversial up to the present day [20,21].…”
Section: Introductionmentioning
confidence: 99%